In vivo virulence of Staphylococcus aureus in native versus prosthetic left-sided valve endocarditisCentral MessagePerspective - Haytham Elgharably, MD; Jan Claesen, PhD; Naseer Sangwan, PhD; Muhammad Etiwy, MD; Penny Houghtaling, MS; Gary W. Procop, MD, MS; Nabin K. Shrestha, MD; Brian Griffin, MD; Jose L. Navia, MD; Lars G. Svensson, MD, PhD; Daniel J. Wozniak, PhD; Gosta B. Pettersson, MD, PhD (JTCVS Open)
Objectives: Staphylococcus aureus infective endocarditis is commonly associated with invasive pathology and is worse in prosthetic valve endocarditis. In this study, we aim to examine S. aureus virulence and pathological features of native and prosthetic valve infective endocarditis. Methods: Between 2002 and 2020, 438 patients underwent surgery for left-sided endocarditis caused by S. aureus at our center (59% native and 41% prosthetic valve endocarditis). Endocarditis registry was queried, and pathological features were based on the echocardiography and operative findings. In addition, vegetation samples were collected from 6 patients undergoing surgery for infective endocarditis (3 native and 3 prosthetic valve endocarditis). Total RNA was extracted from all specimens, and messenger RNA sequencing was executed for transcriptomic analysis. Data were pooled into STAR aligner, and gene expression related to virulence factors was compared between 2 groups. Results: Rates of invasive pathology were higher in prosthetic versus native valve infective endocarditis (76% vs 40%, P < .0001), which impacted the complexity of surgical procedures and perioperative course, but not in-hospital mortality. Transcriptomic analysis has shown differences in gene expression between vegetation specimens of native and prosthetic valve endocarditis, including genes for stress response, biofilm formation, and virulence factors. The gene aur (encodes for aureolysin) was highly upregulated in prosthetic valve vegetations compared with native valve vegetations (P = .023). Conclusions: Prosthetic valve endocarditis caused by S. aureus is associated with further invasive pathology compared with native valve endocarditis, which could be related to upregulation of genes responsible for biofilm formation and metalloproteinase production.